Futurum: um estudo morfossintático sobre o futuro do subjuntivo no português paulistano - Carvalho, Patricia Helena Veloso De [UNIFESP] (2019)
Based on the theoretical assumptions of Gerative Grammar (Cf. Chomsky, 1995, 2001) and Distributed Morphology (Cf. MARANTZ, 1997; EMBICK, 2010), this research makes a morphosyntactic investigation of the future subjunctive (FS) in the adverbs subordinate (temporal and conditional) and relative ones. The data analyzed were extracted from Project SP2010, organized by the Study Group and Research in Sociolinguistics of USP. The data were collected from 2011 to 2013 and correspond to 60 recordings transcribed with ages ranging from 19 to 89 years and different schooling (until high school and higher education). The corpus data were described and analyzed, observing the linguistic variables: connective, time of the verbal form of the main sentence, presence of compound FS and variation between FS and inflected infinitive; and extralinguistic variables: gender, age and schooling. The FS was found in 583 sentences: 488 (83.70%) conditional, 43 (7.38%) temporal and 52 (8.92%) relative. The results indicate that, in the São Paulo variant, FS presents low variation with the verbal form of the inflected infinitive, found only in 13 occurrences; we explain the variation of the verbal form vir to vim, through the operation of impoverishment of the Distributed Morphology; and on the variation of the prefixed verbs, we hypothesize that the speaker has lost the vocabulary items of this type of verbs, thus containing (com + ter) is replaced by an item in list 1, with two different roots for TER √ T- and CONTER √CONT-. The compound FS data was found only in the for + infinitive form ('se você for analisar bem, o Brasil precisa melhorar muito') not described in the grammars consulted. From Perini (1978) and Comrie and Holmback (1984), we list the traits of FS, being: mode (continuum realis-irrealis), aspect, specificity and definiteness; we confirm the temporal correlation between the main and subordinate sentences with FS only in temporal adverbs.